UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN KATANG (Ipomoea pes-caprae L.) ASAL WOLU PROVINSI MALUKU MENGGUNAKAN METODE DPPH - Hasan, Tahirah; Irfayanti, Nur Alfiah; Arifin, Arfiani; Muhammad, Andila Sari (Jurnal Riset Kefarmasian Indonesia, 2024)
Ipomoea pes-caprae (L.) is a plant that comes from the convolvulaceae family and is known to have benefits as antioxidant. This study aims to determine the antioxidant activity of ethanol extract of Maluku's katang leaf (Ipomoea pes-caprae L) against DPPH free radicals. Katang leaves simplicia was extracted using 70% ethanol by maceration Testing of antioxidant activity against DPPH free radicals was analyzed using a viable spectrophotometer at a wavelength of 515 nm. The results of the analysis showed that the antioxidant activity of ethanol extract of katang leaves (Ipomoea pes-caprae L.) had an IC50 value of 92.5266±1.83 pg/mL The antioxidant activity ability of katang leaf extract is 0.066 times compared to ascorbic acid with an IC50 value of 6.12810.07 μg/mL